2004
DOI: 10.1515/hf.2004.007
|View full text |Cite
|
Sign up to set email alerts
|

Solid wood joints by in situ welding of structural wood constituents

Abstract: Mechanically-induced wood flow welding, without any adhesive, is here shown to rapidly yield wood joints satisfying the relevant requirements for structural application. The mechanism of mechanically-induced vibrational wood flow welding is shown to be due mostly to the melting and flowing of the amorphous polymer materials interconnecting wood cells, mainly lignin, but also some hemicelluloses. This causes the partial detachment of long wood cells and wood fibres and the formation of an entanglement network i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 5 publications
2
35
1
Order By: Relevance
“…The adhesion is generated in the interface from the thin layer of molten wood substances after solidification (Gfeller et al 2003). The mechanical performance of the process is frequently investigated by varying the parameters, such as welding time and pressure, amplitude of vibration, and surface quality, and by submitting the welded specimens to shear test according to DIN-EN (2003) 205 (Gfeller et al 2003(Gfeller et al , 2004Ganne-Chédeville et al 2005;Ganne-Chédeville 2008). Ganne-Chédeville et al (2008) observed the behavior of double cantilever beam (DCB) specimens and measured the critical energy release rate (G Ic ) of a welded joint.…”
Section: Introductionmentioning
confidence: 99%
“…The adhesion is generated in the interface from the thin layer of molten wood substances after solidification (Gfeller et al 2003). The mechanical performance of the process is frequently investigated by varying the parameters, such as welding time and pressure, amplitude of vibration, and surface quality, and by submitting the welded specimens to shear test according to DIN-EN (2003) 205 (Gfeller et al 2003(Gfeller et al , 2004Ganne-Chédeville et al 2005;Ganne-Chédeville 2008). Ganne-Chédeville et al (2008) observed the behavior of double cantilever beam (DCB) specimens and measured the critical energy release rate (G Ic ) of a welded joint.…”
Section: Introductionmentioning
confidence: 99%
“…Linear friction welding, i.e., welding with a reciprocating movement, is commonly employed in the thermoplastics and metals industries, and it has shown potential in wood-to-wood connections as well (Sutthoff et al 1996). To highlight the key phenomena within the friction welding process for wood, first certain wood components soften to the point that they even melt and evaporate; second, the components and derivatives form an interphase between the two pieces of wood to be joined by a high-density composite of entangled wood fibres drowned into a matrix of molten wood-intercellular material, such as lignin and hemicelluloses (Gfeller et al 2004;Mansouri et al 2009). The friction welding of wood is characterised by a rapid increase in temperature from ambient up to 220 °C or 450 °C in linear or orbital friction welding, respectively (Stamm et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Welded joints produced by Gfeller et al (2003Gfeller et al ( , 2004) yielded a tensile-shear strength of more than 10 MPa in beech (Fagus sylvatica L.) and 2 MPa in spruce (Picea abies L. Karst.)…”
Section: Introductionmentioning
confidence: 99%
“…[7,10] Wood welding, in the context presented herein, refers to the vibrational bonding method in which only wood is used.…”
Section: Origin and Brief History Of Wood Weldingmentioning
confidence: 99%
“…There are two main branches of wood welding: planar [7,[9][10][11][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and rotational [9,[28][29][30][31][32][33][34][35][36][37][38][39]. Planer is further broken down further into linear vibrational [7,[9][10][11][14][15][16][17][18][19][20][21][22][23][24] and orbital [25][26][27].…”
Section: Planar (Surface) Wood Weldingmentioning
confidence: 99%